Technology-Mediated Collaborative Strategies Among Online University Students - Núñez-Naranjo, Aracelly Fernanda; Quezada-Sarmiento, Pablo Alejandro; Junta, Christian; Orly Carvache-Franco; Lidia Minchenkova; Carvajal, Christian (My University, 2025)
This quasi-experimental study aimed to evaluate the effectiveness of collaborative teaching strategies mediated by digital technologies among online university students. The research was conducted with a sample of 256 participants, divided into an experimental group and a control group. While both groups used technological resources, only the experimental group engaged in structured collaborative strategies using tools such as Genially, Kahoot, Canva, Padlet, and Wordwall, within the framework of the Cátedra Integradora course. The results revealed a significant improvement in the academic performance of the experimental group, with an average increase of 27.4%, compared to 13.2% in the control group. Furthermore, the teacher's perception highlighted higher levels of student engagement, motivation, and collaboration among those who actively participated in the strategies. These findings demonstrate that the intentional use of educational technologies with a collaborative focus fosters active, participatory, and meaningful learning, while also strengthening socio-emotional skills and improving academic achievement in virtual higher education settings. © 2025 IEEE.
Keywords: Active learning; Digital pedagogy; Higher education innovation; Instructional design; Student engagement